Magnetic and electronic properties of La3MO7 and possible polaron formation in hole-doped La3MO7 (M = Ru and Os). (23rd January 2017) - Gao, Bin; Weng, Yakui; Zhang, Jun-Jie; Zhang, Huimin; Zhang, Yang; Dong, Shuai
Abstract: Oxides with 4 d /5 d transition metal ions are physically interesting for their particular crystalline structures as well as the spin–orbit coupled electronic structures. Recent experiments revealed a series of 4 d /5 d transition metal oxides R 3 M O7 ( R : rare earth; M : 4 d /5 d transition metal) with unique quasi-one-dimensional M chains. Here first-principles calculations have been performed to study the electronic structures of La3 OsO7 and La3 RuO7 . Our study confirm both of them to be Mott insulating antiferromagnets with identical magnetic order. The reduced magnetic moments, which are much smaller than the expected value for ideal high-spin state (3 t 2 g orbitals occupied), are attributed to the strong p   −   d hybridization with oxygen ions, instead of the spin–orbit coupling. The Ca-doping to La3 OsO7 and La3 RuO7 can not only modulate the nominal carrier density but also affect the orbital order as well as the local distortions. The Coulombic attraction and particular orbital order would prefer to form polarons, which might explain the puzzling insulating behavior of doped 5 d transition metal oxides. In addition, our calculations predict that the Ca-doping can trigger ferromagnetism in La3 RuO7 but not in La3 OsO7 .